Acaparamiento de tierras y «frágil gobernanza de la tierra» en la frontera agrícola de Matopiba - Silva, Anderson Antonio (2023)
This article contributes to the current debate on the violation of human rights through the practice of green grabbing. The study reflects upon the situation of territorial insecurity and the struggle for territorial rights of the Akroá Gamela people, who live in the south of the State of Piauí, characterized by what is called here weak land governance. The indigenous territory studied does not have its homologation process finalized, which means that it does not officially exist, nor does it allow its boundaries to be added to most of the official databases of different governmental spheres. The region where the Akroá Gamela people are located is also situated within an area of advancing agricultural frontier known as Matopiba, located in the Cerrado area, the second largest biome in Brazil and South America. The main goal is to think on how green grabbing wickedly uses legal problems of communication between entities and governance to foster deforestation. To do so, we analyze two land regulation tools: the Rural and Environmental Registration (CAR) and the Vegetation Suppression Authorization (ASV), to understand this process of traditional population and peasants' land rights encroachment.